Análisis descriptivo del estado de salud en los adultos mayores de la comunidad de Yuracruz, Ibarra, Imbabura. - Hidalgo Proaño, Rafael Germán (2024)
Comprehensive geriatric assessment is a multidisciplinary tool that allows us to evaluate the health status of older adults by applying scales that provide us with data on the level of deterioration of aging in the clinical, functional, cognitive, social and affective sphere of the older adult. Describe the health status of older adults through the measurement of the four spheres of comprehensive geriatric assessment in the community of Yuracruz, during the period October 2023-February 2024. The present study has a quantitative descriptive and field approach, with a non-experimental - cross-sectional design, applying the clinical assessment scales, the Red Cross disability functionality scale and SARCO-GS, the cognitive assessment scale. KIKA-Cog, Gijón socio-familial social assessment scale and the Yesavage affective assessment scale through the use of the interview as a data collection technique and the management of descriptive statistics as the data analysis and interpretation technique. The results obtained through the use of the assessment scales of the 39 older adults AM show us that the predominant age range is between 75 - 84 years with 55% (12) men and 59% (10) women , are reflected in the results that more than 80% of MAs present a disability and 95% present sarcopenia, 92% present signs of possible dementia, 72% indicate a social risk and 28% have a social problem and can be show that there is a homogeneous percentage with 44% mild depression and 44% established depression in the older adult population of the rural community of Yuracruz.